Castleman's disease in a patient with melanoma: the role of VEGF. (30th April 2012) - Shahani, Lokesh
Abstract : Castleman's disease is a rare lymphoproliferative disorder characterised by lymph node follicular hyperplasia with abnormal interfollicular vascular growth. The authors report a female patient presenting with erythematous and pruritic skin lesion. A shave biopsy of the lesion revealed a Clark level III melanoma and sentinel lymph node biopsy revealed a microscopic focus. Staging positron emission tomography scan revealed an abnormal soft tissue mass with increased 18F-fluorodeoxyglucose accumulation in the anterior mediastinum, raising suspicions of malignancy. The patient underwent an elective resection of the mass and histological sections revealed features of Castleman's disease of the hyaline vascular type. Vascular endothelial growth factor (VEGF) has been associated with the increased vessel density in this condition. VEGF secretion by tumour cells in solid tumours such as melanomas could be a predisposing factor for Castleman's disease. Future research is needed to find an association between VEGF-secreting solid tumours and the development of lymphoproliferative tumours such as Castleman's disease.